Congenital neuroblastoma with symptoms of epidural compression at birth. (17th February 2016) - Gigliotti, A. R.; De Ioris, M. A.; De Grandis, E.; Podda, M.; Cellini, M.; Sorrentino, S.; De Bernardi, B.; Paladini, D.; Gandolfo, C.
ABSTRACT: The occurrence of congenital neuroblastoma presenting at birth with symptoms of epidural compression secondary to spinal canal invasion is rare. Almost all cases reported in the literature have survived from the tumor but suffer severe sequelae, with the exception of the 2 most recently described whose birth was anticipated. The 3 cases of this article have been followed for a minimum of 5 years with the aim to describe their definitive late complications. In none of these cases had the routine ultrasound scan performed in third trimester of pregnancy discovered a tumor mass, nor had it shown abnormal fetal movements. All had leg hypotonia detected on the first day of life. In all, both primary and intraspinal tumors responded well to chemotherapy. All survive with motor deficit and severe bladder dysfunction despite early physiotherapy. Scoliosis has developed in the case with the longest follow-up. The description of these patients enforces the importance of early diagnosis of tumor masses in late pregnancy. Neonatologists should be aware of this rare clinical entity and take it into account in the differential diagnosis with other conditions of early-onset hypotonia. On the other hand, obstetric sonologists should be aware of the possibility to detect such rare tumors in late pregnancy, as anticipation of delivery may reduce the risk of late sequelae.